2006
DOI: 10.4319/lo.2006.51.1.0288
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient and light availability regulate the relative contribution of autotrophs and heterotrophs to respiration in freshwater pelagic ecosystems

Abstract: In this study, two main hypotheses were addressed. (1) Bacteria contribute proportionally less than autotrophs to ecosystem respiration as trophic status increases. This hypothesis was examined in a pond phosphorus-fertilization experiment and two microcosm nutrient-fertilization experiments. (2) The relative contribution of autotrophs to ecosystem respiration, at a given nutrient availability, increases as light availability increases. This hypothesis was tested in three light by nutrient factorial microcosm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 56 publications
2
32
1
1
Order By: Relevance
“…Total respiration tends to increase with lake trophy, and respiration by autotrophs becomes an increasing part of total respiration as lakes become more eutrophic (del Giorgio and Peters, 1993;Biddanda et al, 2001;Roberts and Howarth, 2006). A literature review by del Giorgio and Peters (1993) suggests that autotrophic respiration may contribute 35% in oligotrophic systems and over 60% in eutrophic systems.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Total respiration tends to increase with lake trophy, and respiration by autotrophs becomes an increasing part of total respiration as lakes become more eutrophic (del Giorgio and Peters, 1993;Biddanda et al, 2001;Roberts and Howarth, 2006). A literature review by del Giorgio and Peters (1993) suggests that autotrophic respiration may contribute 35% in oligotrophic systems and over 60% in eutrophic systems.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Several studies have indicated that the contribution to community respiration of bacteria relative to phytoplankton decreases with increasing nutrient availability because of increases in phytoplankton respiration (Biddanda et al 2001, Chan et al 2004). Furthermore, Roberts & Howarth (2006) found that the bacterial contribution to respiration is lower when light availability for photosynthesis increases. According to the results of nutrient addition experiments performed by Roberts & Howarth (2006), the variability patterns of community respiration following nutrient enrichment are related to the higher metabolic needs of phytoplankton growing actively, while bacterial respiration remains more stable.…”
Section: Changes In Bacterial Metabolism and Plankton Community Respimentioning
confidence: 99%
“…Furthermore, Roberts & Howarth (2006) found that the bacterial contribution to respiration is lower when light availability for photosynthesis increases. According to the results of nutrient addition experiments performed by Roberts & Howarth (2006), the variability patterns of community respiration following nutrient enrichment are related to the higher metabolic needs of phytoplankton growing actively, while bacterial respiration remains more stable. In our experiments, the main factor contributing to variability of RR was light (Table 1), supporting the hypothesis that the changes in RR were related to changes in phytoplankton respiration (direct effects of irradiance level on bacterial respiration can be discarded).…”
Section: Changes In Bacterial Metabolism and Plankton Community Respimentioning
confidence: 99%
“…Such a change in light climate is of great importance to the local ecosystem. Light availability has recently been pointed out as the main controlling factor of the relative contribution of the phytoplankton and bacteria on total community respiration (Roberts and Howarth 2006). While bacterial respiration rates remain roughly constant under differing light conditions, increased light intensity can increase the respiration rates of the phytoplankton to over 90% of the total planktonic respiration (Roberts and Howarth 2006).…”
Section: Discussionmentioning
confidence: 99%